1998
DOI: 10.1016/s0378-5955(98)00079-3
|View full text |Cite
|
Sign up to set email alerts
|

Development of the base of the cochlea: place code shift in the gerbil

Abstract: Distortion product otoacoustic emission measurements were made at 1/12 octave intervals before and after the injection of furosemide in gerbils aged 15 days after birth to adult, in order to obtain estimates of cochlear amplifier gain as a function of stimulus frequency. The frequency at which the gains went sharply to zero, defined as the`base cutoff frequency', increased from about 20 kHz to over 50 kHz during development. This increase provides further confirmation of the hypothesis that the place code chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 38 publications
2
4
1
Order By: Relevance
“…Novel and potentially important as the suggestion of Overstreet et al (2002b) may prove to be, data collected from a variety of laboratories support the alternative position. Specifically, aside from the findings of McGuirt et al (1995), whose endocochlear potential and compound action potential findings are in line with the suggestion of Overstreet et al (2002b), others have shown that the sensitivity of gerbils to tone bursts in the 35-kHz range are mature by 20 postnatal days of age, as is the endocochlear potential and all other aspects of passive transduction (McFadden et al 1996;Mills and Rubel 1998;Norton et al 1991;Ryan 1984, 1988). Nonetheless, if the suggestion of Overstreet et al (2002b) proves to be an accurate characterization of basilar membrane development in the extreme base of the cochlear spiral, it will be important to determine whether the developmental dynamic that governs transduction at that location generalizes to the rest of the cochlea.…”
Section: Discussionsupporting
confidence: 54%
“…Novel and potentially important as the suggestion of Overstreet et al (2002b) may prove to be, data collected from a variety of laboratories support the alternative position. Specifically, aside from the findings of McGuirt et al (1995), whose endocochlear potential and compound action potential findings are in line with the suggestion of Overstreet et al (2002b), others have shown that the sensitivity of gerbils to tone bursts in the 35-kHz range are mature by 20 postnatal days of age, as is the endocochlear potential and all other aspects of passive transduction (McFadden et al 1996;Mills and Rubel 1998;Norton et al 1991;Ryan 1984, 1988). Nonetheless, if the suggestion of Overstreet et al (2002b) proves to be an accurate characterization of basilar membrane development in the extreme base of the cochlear spiral, it will be important to determine whether the developmental dynamic that governs transduction at that location generalizes to the rest of the cochlea.…”
Section: Discussionsupporting
confidence: 54%
“…For sound levels above about 40 dB SPL (sound pressure level, dB re 2 ´10 -5 Pa), responses are compressed, allowing representation of the dynamic range of cochlear responses within the scope of the auditory nerve fiber's neural signaling [3][4][5][6] . Acoustic distortion measurements 16,17 and, more directly, specific basilar membrane lesions 18 and measurements of the longitudinal distribution of basilar membrane vibrations to tones of a single frequency 19 indicate that OHCs located near the CF position contribute to local basilar membrane tuning, and, for high-level tones, less than 400 OHCs are actively involved over 1.2 mm. In the basal turn of the guinea pig cochlea, precise frequency tuning of the basilar membrane is reflected in the voltage responses of the OHCs to tones 14 .…”
Section: Articlesmentioning
confidence: 99%
“…These include tonotopy (de Villers-Sidani et al 2007), binaural matching of frequency tuning (Polley et al 2013), and the laminar and topographic organization of feedforward TC functional response profiles (Barkat et al 2011). One notable exception can be found in the cortical sensitivity to airborne tone bursts, which increases 100-fold (i.e., 40 dB) between P11 and P14 in accordance with the commensurate maturation of ear canal patency and cochlear biomechanics that also unfold during this brief period (Adise et al 2014; Mikaelian et al 1965; Mills and Rubel 1998). However, the dynamic expression levels of VGluT1, VGluT2, and VGAT in conjunction with changes in the intrinsic membrane properties (Metherate and Cruikshank 1999; Oswald and Reyes 2011) and ligand-gated receptor composition (Hsieh et al 2002; Venkataraman and Bartlett 2013, 2014) in the auditory forebrain between P11 and P14 suggest that the rapid maturation of sound-evoked responses measured in A1 and MGB of intact animals during the first days of hearing may reflect a combination of peripheral and central changes.…”
Section: Discussionmentioning
confidence: 93%